If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -10 = -10 Reorder the terms: -10 + 2x = -10 Add '10' to each side of the equation. -10 + 10 + 2x = -10 + 10 Combine like terms: -10 + 10 = 0 0 + 2x = -10 + 10 2x = -10 + 10 Combine like terms: -10 + 10 = 0 2x = 0 Solving 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 0 Simplifying x = 0
| 1-8x=-13+2x-8x | | 3x+2(6x+11)=157 | | 2x^2+36-2295=0 | | 5x+13=2x+4 | | 1+x=2+x | | (2w-1)(2w-1)=4(w-3)(w-3) | | (10x^3y^3-15x^2y^3-15y^2)/(5xy^2) | | b-6=-4+3b | | v=1/3(3.14)(1.5)(1.5)(h) | | 3x+3(5x+16)=174 | | 5x=2x-2 | | -m+2m+6=m+6 | | 3/4×y=6 | | 9x^2-10x=-1 | | y=1/3(9)-1 | | 4-2x=-5-5x | | 2x+5=250 | | y=1/3(3)-1 | | 5-(2x-3)=8+2x | | -13+3x=8x+8x | | -6z+6+7z=11 | | x^4-x^3-5x^2=0 | | 427-51x=180 | | 4x+7(x-9)=69 | | x+0.07x=282.68 | | -14-4r=-2+8r | | 6x+y=27 | | 7k+8+8k=11+5+4k+3k | | 5y-3y=27 | | 3x+7(5x-5)=193 | | 2t+-1=3t+7 | | 3b-5=-7+2b |